Disfunção miocárdica sistólica pela ecocardiografia feature tracking bidimensional em cães naturalmente infectados por parvovírus - Abreu, Claudine Botelho de (2017)
Parvovirus infects cells with high mitotic activity, such as enterocytes, lymphoid tissues, bone marrow, and occasionally the myocardium of pups. Parvovirus myocarditis may also be secondary to sepsis, since this condition often leads to myocardial dysfunction. Conventional echocardiographic techniques, routinely used as a noninvasive examination for the evaluation of myocardial function, are subjective and semiquantitative. The present study evaluated systolic myocardial dysfunction in dogs naturally infected with parvovirus using two-dimensional feature tracking echocardiography. Thirty-seven dogs were evaluated, divided into non-infected group (n = 9), infected group without sepsis (n = 15) and group infected with sepsis (n = 13). The values of global strain and strain rate and of six myocardial segments in the radial, circumferential and longitudinal directions were obtained in the transverse right parasternal (short axis) and apical four chambers in the left ventricle. Circumferential and longitudinal strain and strain rate were still obtained at endocardial and epicardial levels. In general, mean of global, endocardial, epicardial and overall segments strain and strain rate was statistically higher in the non-infected group than in infected groups; in the sepsis group was statistically lower than in the group without sepsis. The segments commonly affected in both infected groups were endocardial middle septal, and basal and middle laterals. There are no changes in the conventional echocardiographic variables. In the intraobserver evaluation, the variability was low for all variables of strain and strain rate, and in the interobserver, low for circumferential, moderate for radial and high for longitudinal. It is concluded that (1) parvovirus infection in dogs causes systolic dysfunction, being greater extent in animals with sepsis, and with probable onset in the endocardial middle septal, basal and middle lateral regions; and (2) feature tracking echocardiography is more sensitive and precocious than conventional echocardiography in determining systolic dysfunction.